Stemming the Revolving Door: Teacher Retention and Attrition in Arctic Alaska Schools - Kaden, Ute; Patterson, Philip P.; Healy, Joanne; Adams, Barbara L. (Mercy University, New York, 2016)
Limited research is available concerning teacher retention and teacher attrition in Arctic Alaska.┬á This paper reports survey research findings, which identify factors related to teacher retention and attrition in Alaskan Arctic Native┬ácommunities. Teacher retention rates (2009-2013) vary widely over time showing no significant trends. Results confirm that teacher turnover in rural districts is higher than in urban school districts.┬áThe authors recognize that teacher retention and attrition are multidimensional issues recommending that better communication patterns and shared responsibilities between rural school districts, local administrators, teachers, community members, and university-based teacher preparation programs be established.